Fetomaternal outcome in placenta previa - a retrospective study in teaching hospital - Rangaswamy, Manohar; Govindaraju, Kayvashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prevalence of Placenta previa is found to vary between 0.5% of all pregnancies. Placenta previa is one of the major causes of antepartum hemorrhage and is also important cause of maternal and perinatal morbidity and mortality in India. Methods: This is a retrospective study conducted in department of OBG, Mandya Institute of Medical Science, Mandya for a period of five years from January 2011 to December 2015. All cases of placenta previa during pregnancy admitted during this period were included in the study. All case records were obtained from medical record section and carefully analyzed to find out the incidence, various types of placenta previa, its clinical presentation and its outcome in relation to mode of delivery, birth weight, and maternal, maternal and perinatal morbidity. Results: The prevalence of placenta previa was 0.2% and was more commonly present among multiparous women (75.8%). Most common type was type 1 placenta previa in 23 (37.2%) cases followed by type 2 in19 cases (30.6%). 13 cases (20.9%) were of complete placenta previa which was similar to study conducted by Vaishali et al. Out of 62 cases, 10 (16.1%) had atonic PPH and 2 cases underwent peripartum hysterectomy. All cases of perinatal mortality were between 28 to 30 weeks weighing between 1-1.2 kg associated with complete placenta previa in 3 cases and type 3 (incomplete) in 2 cases. There was no maternal mortality in this study. Conclusions: Managing a case of placenta previa during pregnancy poses a great challenge to every obstetrician in present day obstetrics due its increased risk of maternal and perinatal complications.